2015
DOI: 10.1017/s1366728914000406
|View full text |Cite
|
Sign up to set email alerts
|

Two languages, one effect: Structural priming in spontaneous code-switching

Abstract: We investigate here the contribution of code-switching and structural priming to variable expression of the Spanish first person singular subject pronoun in the New Mexican bilingual community. Comparisons with both Spanish and English benchmarks indicate no convergence of Spanish toward English grammar, including in the presence of code-switching, where the linguistic conditioning of variant selection remains unaltered. We find a language-internal and cross-language priming effect, albeit of differing strengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 58 publications
1
45
1
1
Order By: Relevance
“…This view of competence in bilinguals, as different from monolinguals, is also compatible with MULTIPLE GRAMMARS THEORY (Amaral & Roeper, 2014), which suggests that the language faculty accommodates contradictory linguistic rules. Our proposal that bilingual experience might trigger language change is based on sentence-level structure and formulated using experimental evidence, but this preliminary idea also complements existing proposals from other domains regarding the mechanisms influencing diachronic language change, most significantly from corpus studies in the variationist sociolinguistics and cognitive linguistics traditions (e.g., Otheguy, Zentella & Livert, 2007;Silva-Corvalán, 1994;Torres Cacoullos & Travis, 2015;Dogruöz & Backus, 2009). Another related domain is research on phonological change documenting how unintentional errors and imitations lead to long-term change (e.g., Harrington, 2012).…”
Section: Introductionmentioning
confidence: 72%
“…This view of competence in bilinguals, as different from monolinguals, is also compatible with MULTIPLE GRAMMARS THEORY (Amaral & Roeper, 2014), which suggests that the language faculty accommodates contradictory linguistic rules. Our proposal that bilingual experience might trigger language change is based on sentence-level structure and formulated using experimental evidence, but this preliminary idea also complements existing proposals from other domains regarding the mechanisms influencing diachronic language change, most significantly from corpus studies in the variationist sociolinguistics and cognitive linguistics traditions (e.g., Otheguy, Zentella & Livert, 2007;Silva-Corvalán, 1994;Torres Cacoullos & Travis, 2015;Dogruöz & Backus, 2009). Another related domain is research on phonological change documenting how unintentional errors and imitations lead to long-term change (e.g., Harrington, 2012).…”
Section: Introductionmentioning
confidence: 72%
“…As noted, almost all research on structural priming in bilinguals has been experimental, a development that is somewhat at odds with the growing number of studies on within-language priming that use corpus data. Recently, however, large-scale bilingual corpora have become accessible and the first corpus-based priming studies have been done (e.g., Fricke & Kootstra, 2016; Torres Cacoullos & Travis, 2013, 2016; Travis et al, 2017). To be able to interpret and appreciate this corpus-based work with reference to previous research on within-language and cross-linguistic priming (in Section 4), it is first necessary to recap the evolution of corpus work in priming research, which is the topic of the next section.…”
Section: Cross-linguistic Primingmentioning
confidence: 99%
“…All of these studies show that priming can be studied corpus-linguistically, that such studies do not necessarily inflate priming results as may have been feared (because of the noisiness and collinearity that are much more characteristic of corpus data than of experimental data), and that different types of persistence may be distinguished. In addition, corpus data allow the researcher to study more words, prime-target distances, registers, or any other kind of moderator variables than most experimental studies would, as well as to explore the phenomenon in ecologically more valid scenarios: one can easily include lexically-specific frequencies and baseline frequency effects in the analyses and avoid exposing subjects to unnatural stimuli or stimulus distributions potentially leading to within-experiment learning effects (e.g., Schütze, 1996: Section 5.2.3, Gries & Wulff, 2009, Jaeger, 2010, Doğruöz & Gries, 2012, Torres Cacoullos & Travis, 2013, and others), which should therefore also be included in the statistical modeling of priming effects in experimental studies (see e.g., Kootstra & Doedens, 2016, for an example of this). Given the resulting complexity, the movement towards GLMMs, which is now also becoming the standard in experimental studies, is a welcome development: they avoid conflating individual data points into proportions per lexical item and/or participant which make it difficult, for instance, to explore within-subject accumulative priming effects of the type explored by Gries and Wulff (2009); avoid different ANOVAs on different constructional choices (as in Savage et al, 2003) or successive experiments by allowing one to combine datasets and probe interactions between the predictors and a variable coding for datasets; the corpus-linguistic parallel to this would be to not do separate analyses on different speakers or different corpora, but include indicator variables for corpora and speakers as predictors or random effects; avoid unnecessary methodological decisions such as the factorization of numerical data; provide a state-of-the-art approach towards handling data points that exhibit dependencies including crossed random effects (speakers and/or lexical items) as well as nested random effects (registers/conversations/speakers) and can handle data even if they violate assumptions of repeated-measures ANOVAs (such as sphericity). …”
Section: The Development Of Corpus-based Studies On Within-language Pmentioning
confidence: 99%
See 1 more Smart Citation
“…Bilinguals switch quite frequently and naturally from one language to the other, both between or within sentences (Appel and Muysken, 2005: 80). Some argue that code-switching fosters grammatical change in bilingual contact situations (see Torres Cacoullos and Travis, 2016: 1 for an overview); yet, others have shown that up until now, little evidence for code-switching having an effect on contact-induced change has been put forward (see Poplack and Levey, 2010;Torres Cacoullos and Travis, 2016).…”
mentioning
confidence: 99%